Frailty as a predictor of mortality: a comparative cohort study of older adults in Costa Rica and the United States - Carolina Santamaría-Ulloa; Amanda J. Lehning; Mónica V. Cortés-Ortiz; Ericka Méndez-Chacón (BMC, 2023)
Abstract Background Frailty is a common condition among older adults that results from aging-related declines in multiple systems. Frailty increases older adults' vulnerability to negative health outcomes, including loss of mobility, falls, hospitalizations, and mortality. The aim of this study is to examine the association between frailty and mortality in older adults from Costa Rica and the United States. Methods This prospective cohort study uses secondary nationally-representative data of community-dwelling older adults from the Costa Rican Longevity and Healthy Aging Study (CRELES, n = 1,790) and the National Health & Aging Trends Study (NHATS, n = 6,680). Frailty status was assessed using Physical Frailty Phenotype, which includes the following five criteria: shrinking, exhaustion, low physical activity, muscle weakness, and slow gait. We used Cox proportional hazard models to examine the association between frailty and all-cause mortality, including sociodemographic characteristics and health behaviors as covariates in the models. Mortality follow-up time was right censored at 8 years from the date at baseline interview. Results The death hazard for frail compared to non-frail older adults was three-fold in Costa Rica (HR = 3.14, 95% CI: 2.13-4.62) and four-fold in the White US (HR = 4.02, 95% CI: 3.04-5.32). Older age, being male, and smoking increased mortality risk in both countries. High education was a protective factor in the US, whereas being married/in union was a protective factor in Costa Rica. In the US, White older adults had a lower risk of death compared to all other races and ethnicities. Conclusions Results indicate that frailty can have a differential impact on mortality depending on the country. Access to universal health care across the life course in Costa Rica and higher levels of stress and social isolation in the US may explain differences observed in end-of-life trajectories among frail older adults.